02.08: The influence of plate thickness on the welding residual stresses from submerged arc welding in offshore steel structures. (13th September 2017) - Andreassen, Michael Joachim; Yu, Zhenzhen; Liu, Stephen; Nielsen, Jens Henrik
ABSTRACT: Welding‐induced residual tensile stresses and distortion have become a major concern in relation to the structural integrity of welded structures within the offshore wind industry. The stresses have a negative impact on the integrity of the welded joint, as they promote distortion, reduce fatigue life, and attribute to the corrosion cracking and brittle fracture in the weld components. This study investigates the influence of plate thickness on the welding‐induced residual stresses. The residual stresses are investigated through experiments and in accordance with existing production procedures leading to a better understanding of the distribution and development of the welding residual stresses. This can later be used to optimize the fatigue design, providing a more efficient and improved design. In this context, the current research is expected to benefit the offshore industry by leading to an improved design, which consequently may be included in future norms and standards. Submerged Arc Welding (SAW) was used to make a fully penetrated butt weld in 10 mm and 40 mm thick steel plates with the same welding parameters as used in the production procedures. The base material is thermomechanical hot‐rolled low‐carbon fine‐grained S355ML steel in accordance with the European standard DS/EN 10025‐4 [1]. The welding temperature profile during welding was recorded by embedded thermocouples and the hole‐drilling method was used to measure the near‐surface residual stress state.